Carbon-Coated Three-Dimensional MXene/Iron Selenide Ball with Core–Shell Structure for High-Performance Potassium-Ion Batteries - Yang, Su Hyun; Lee, Yun Jae; Kang, Heemin; Park, Seung‑Keun; Kang, Yun Chan (Nano-Micro Letters, 2021)
Two-dimensional (2D) MXenes are promising as electrode materials for energy storage, owing to their high electronic conductivity and low diffusion barrier. Unfortunately, similar to most 2D materials, MXene nanosheets easily restack during the electrode preparation, which degrades the electrochemical performance of MXene-based materials. A novel synthetic strategy is proposed for converting MXene into restacking-inhibited three-dimensional (3D) balls coated with iron selenides and carbon. This strategy involves the preparation of Fe2O3@carbon/MXene microspheres via a facile ultrasonic spray pyrolysis and subsequent selenization process. Such 3D structuring effectively prevents interlayer restacking, increases the surface area, and accelerates ion transport, while maintaining the attractive properties of MXene. Furthermore, combining iron selenides and carbon with 3D MXene balls offers many more sites for ion storage and enhances the structural robustness of the composite balls. The resultant 3D structured microspheres exhibit a high reversible capacity of 410 mAh g−1 after 200 cycles at 0.1 A g−1 in potassium-ion batteries, corresponding to the capacity retention of 97% as calculated based on 100 cycles. Even at a high current density of 5.0 A g−1, the composite exhibits a discharge capacity of 169 mAh g−1. Highlights: 1 We propose a novel synthetic strategy for converting MXene nanosheets into 3D balls coated with iron selenides and carbon (FeSex@C/MB), using the ultrasonic spray pyrolysis and thermal treatment. 2 Combining iron selenides and carbon with 3D MXene balls offer many more sites for ion storage and enhance the structural robustness of the composite balls. 3 The resultant shows high electrochemical performances when used in potassium-ion battery in terms of cycling stability and rate capability.